Ways out of the maze in Nigeria? A Review of: “Naija Marxisms: Revolutionary Thought in Nigeria” by Adam Mayer - Suha, György (Journal of Central and Eastern European African Studies, 2024)
A Review of: “Naija Marxisms: Revolutionary Thought in Nigeria” by Adam Mayer